2012
DOI: 10.1002/aic.13904
|View full text |Cite
|
Sign up to set email alerts
|

Laminar‐forced convection mass transfer to ordered and disordered single layer arrays of spheres

Abstract: Laminar forced convection mass transfer to single layers of equidistantly and nonequidistantly spaced spheres perpendicular to the flow direction is studied. Average Sherwood numbers are reported as a function of geometric configurations and flow conditions, for open frontal area fractions between 0.25 and 0.95, Schmidt numbers between 0.7 and 10, and Reynolds numbers (based on the sphere diameter and the free stream velocity) between 0.1 and 100. For equidistantly spaced arrays of spheres, a general analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…All our simulations are two‐dimensional (2‐D), and as a consequence the carbon particles are modeled as thin, infinitely long cylindrical fibers with their axes perpendicular to the flow direction. In a previous study, we have shown that, for a given open frontal area, the mass transfer to such fibers differs little from that to spherical particles. The air gap thickness δ g is uniform along the angular direction θ in all our simulations.…”
Section: Numerical Modelmentioning
confidence: 99%
“…All our simulations are two‐dimensional (2‐D), and as a consequence the carbon particles are modeled as thin, infinitely long cylindrical fibers with their axes perpendicular to the flow direction. In a previous study, we have shown that, for a given open frontal area, the mass transfer to such fibers differs little from that to spherical particles. The air gap thickness δ g is uniform along the angular direction θ in all our simulations.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Numerical simulations are potentially part of their toolbox. The equations to be solved are largely known, and so are the basic material properties (most notably viscosities and diffusion coefficients) and there are many examples of successful applications of numerical solutions to heat and mass transfer problems in fluid‐solid systems …”
Section: Introductionmentioning
confidence: 99%